Climate Risk Management in Insurance: Exploring the Relationship between Global Greenhouse Gas Emissions and Premium Pricing - J. Leo (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Climate change continues to pose enormous risks to global ecosystems and economies. Understanding the impact of climate change on the insurance business is critical for efficient risk management and mitigation of effort. This study looks into the relationship between global greenhouse gas (GHG) emissions and premium pricing in the insurance industry, with an emphasis on the implications for climate risk mitigation. A regression analysis is performed using historical premium data from Organisation for Economic Co-operation and Development (OECD) countries and globally GHG emissions data to investigate the relationship between these variables. The findings show a substantial positive association between GHG emissions and insurance premiums, implying that rising levels of GHG emissions are associated with higher premium prices. This study points out the significance of including environmental issues into insurance risk assessment and pricing models in order to properly account for climate-related hazards. These findings have implications for climate risk management in the insurance business, highlighting the need for proactive actions to meet the mounting difficulties posed by climate change.